(untitled) (Albayan Scientific Journal, 2023)
The Most Popular Leadership Patterns for the Head of Scientific Department at Omar Al-Mukhtar University, El-Beida, By the Viewpoint of Faculty Members Abstract: The main aim of the research is to identify the leadership patterns prevailing among the heads of scientific departments at Omar Al-Mukhtar University in El-Bayda, from the viewpoint of the faculty members, and the research sample consisted of 265 faculty members (male/female). The questionnaire was used to collect field data. That the most popular pattern was the autocratic, followed by the democratic, then the laissez-faire. And that there are statistically significant differences, between the three patterns according to the variable of the respondents’ gender, And that there are not statistically significant differences at leadership patterns as a whole according to the variable of the faculties type. However, that there are statistically significant differences between the three patterns according to the variable of the faculties type.